Fast 2D super resolution ISAR imaging method under low signal‐to‐noise ratio. Issue 10 (7th September 2017) - Li, Shaodong; Chen, Wenfeng; Liu, Weijian; Yang, Jun; Ma, Xiaoyan
Abstract : Sparse representation (SR)‐based inverse synthetic aperture radar (ISAR) imaging method can achieve super‐resolution image of a target. However, it is computationally expensive and sensitive to noise. To overcome these two drawbacks, the authors propose the coupled Nesterov linearised Bregman iteration algorithm based on two–dimensional (2D) real‐valued dictionaries (CNLBI‐TRD) for ISAR imaging. First, the ISAR echoes are taken as a 2D joint SR model in the range frequency‐azimuth Doppler domain. Then the 2D complex‐valued dictionaries are converted into real‐valued ones through unitary transformations. The computational complexity is thus decreased by a factor of at least four. Finally, the CNLBI algorithm is proposed to reconstruct the 2D SR model directly. It combines the Nesterov's accelerated gradient method with the condition number optimisation of sensing matrices. An adaptive‐adjustment strategy of the soft threshold parameter is presented. Thus the total iteration numbers can be greatly reduced. The simulation results and real data experiments verify the effectiveness of the proposed imaging algorithm.